High-density genetic mapping identified QTLs for anaerobic germination tolerance in rice - Liang, Wenhua; Du, Hongyang; Pang, Bingwen; Cheng, Junjie; He, Bing; Hu, Fengqin; Lv, Yuanda; Zhang, Yadong (Frontiers in Plant Science, 2022)
In the study, recombinant inbred lines population of TD70 Japnica cultivar and Kasalath indica cultivar, was employed to construct a high-density genetic map by whole genome re-sequencing. A total of 50 QTLs were detected for CL(coleoptile length), CD(coleoptile diameter), CSA(coleoptile surface area) and CV(coleoptile volume) related traits in the two stages of anaerobic treatment with using complete interval mapping method (inclusive composite interval mapping, ICIM). Among the four traits associated with coleoptile, coleoptile volume had the largest number of QTLs (17), followed by coleoptile diameter (16), and coleoptile length had 5 QTLs. These QTLs could explain phenotypic contribution rates ranging from 0.34% to 11.17%, and LOD values ranging from 2.52 to 11.57. Furthermore, 12 stable QTLs were used to detect the aggregation effect analysis. It was found that individuals with more aggregation synergistic alleles had higher phenotypic values in different environments. In this study, QTL mapping and aggregation effect analysis of different loci related to the anaerobic germination of rice seeds were conducted to lay a foundation for the fine mapping of related genes in subsequent assisted breeding.